Same day discharge after atrial fibrillation ablation is feasible and safe. Results of a prospective study in 1015 patients. (14th October 2021) - Viezelis, M; Pontoppidan, J; Johansen, J.B; Djurhuus, S.M; Dalhoj, J; Asferg, C; Osmanagic, A; Sandgaard, N.C.F
Abstract: Background: Atrial fibrillation (AF) ablation is the standard treatment for symptomatic paroxysmal and persistent AF. It is a common practice for patients to stay overnight after the ablation for observation of possible complications. Thus, increasing volume of procedures places a significant strain on institutions. To tackle this issue, our institution developed a same-day discharge (SDD) protocol for AF ablation. Purpose: To assess the feasibility and safety of the SDD protocol after at least four-hour observation in patients undergoing radiofrequency ablation (RFA) for AF. Methods: A SDD protocol was implemented in our institution in March 2019. We conducted a prospective observational study that included all consecutive patients who underwent ablation for AF until January 2021. A detailed workflow setup provided in the figure. To compare means the Mann Whitney U test, and for categorical variables – χ 2 test were used. The difference was significant when p<0.05. Results: A total of n=1015 patients underwent RFA in the study period. Of those, same-day discharge was feasible in n=751 (74.1%) and n=264 stayed overnight. The mean age (SDD 62.5 SD 8.8 years vs overnight-stay 64.1 SD 9.2 years, p=0.105) and gender distribution (males SDD 46.8% vs overnight-stay 39.8%, p=0.265) did not differ between the two groups. In the SDD group no patients were readmitted for complications within 24 hours after the ablation. A severe complication was defined as pericardial effusion with drainage, pulmonary oedema, thromboembolic event and vascular complication needing surgical intervention. In total 3.0% of all patients experienced a severe complication. The main reasons for staying overnight were small groin hematoma without intervention (18.9%), nausea (14.4%) and logistic issues (32.2%). The 30-day hospital readmission rate was insignificantly higher in the overnight-stay group (19.4% vs 28.0%, p=0.113). The most common reasons for readmission were arrhythmias (SDD 10.1% vs overnight-stay 20.5%) and chest pain (SDD 7.6% vs overnight-stay 2.4%). One late pericardial effusion with drainage on day 10 after the ablation was noted in the SDD group. Conclusion: Same-day discharge in patients after RFA for AF is feasible and safe with an observational period of at least four hours and immediate transthoracic echocardiography after the procedure. Funding Acknowledgement: Type of funding sources: None.